Faktor Dominan yang berhubungan dengan Kualitas Tidur pada Mahasiswa Fakultas Keperawatan Universitas Airlangga - Dhimas Wahyu Wicaksono; Ah Yusuf; Ika Yuni Widyawati (Universitas Airlangga, 2019)
Introduction: Rest and sleep were human base necessary. Sleep quality was human satisfied for sleep, so that human not felt tired, not easier stimulated and nervous, not weak and apathies, no blackness around eyes, no swollen eyelid, no red conjunctiva, no poignant eyes, no difficulties to concentrate, no headache, or often felt sleepy. The aimed of this study was to explain the dominant correlation factors of sleep quality in Faculty of Nursing student Airlangga University.Methods: This research was used Descriptive Analyze Design. Population was Faculty of Nursing student Airlangga University stayed in Mulyorejo-Surabaya in Juni 2012. The samples were 50 taken with purposive sampling technique. Data were collected with questionnaire and were analyzed with spearman’s rho with significance level was p<0.05.Result: The result showed that some factors had significance correlation but some were not. The factors were had significance correlation were between stress and sleep quality (p=0.024), tired with sleep quality (p=0.001), illness with sleep quality (p=0.022). Some factors were had no correlation were between environment with sleep quality (p=0.497), diet with sleep quality (p=0,201), drug with sleep quality (p=0.731), and lifestyle with sleep quality (p=0.816).Discussion: stress, tired, and illness were dominant factorswhich were influence sleep quality for Faculty of Nursing student Airlangga University. Further research should occupied larger amount of sample to make more representative population.